Stable expression of rat cytochrome P-450IIB1 cDNA in Chinese hamster cells (V79) and metabolic activation of aflatoxin B1. - Doehmer, J (1988)
V79 Chinese hamster fibroblasts are widely used for mutagenicity testing but have the serious limitation that they do not express cytochromes P-450, which are needed for the activation of many promutagens to mutagenic metabolites. A full-length cDNA clone encoding the monooxygenase cytochrome P-450IIB1 under control of the simian virus 40 early promoter was constructed and cointroduced with the selection marker neomycin phosphotransferase (conferring resistance to G418) into V79 Chinese hamster cells. G418-resistant cells were selected, established as cell lines, and tested for cytochrome P-450IIB1 expression and enzymatic activity. Two cell lines (SD1 and SD3) were found that stably produce cytochrome P-450IIB1. Although purified cytochromes P-450 possess monooxygenase activity only after reconstitution with cytochrome P-450 reductase and phospholipid, the gene product of the construct exhibited this activity. This implies that the gene product is intracellularly localized in a way that allows access to the required components. If compared with V79 cells, the mutation rate for the hypoxanthine phosphoribosyltransferase (HPRT) locus in SD1 cells is markedly increased when exposed to aflatoxin B1, which is activated by this enzyme.